Using Information Technology to Add Value to Management Education - Alavi, Maryam; Yoo, Youngjin; Vogel, Doug (Academy of Management Journal, 1997)
This article describes the design and delivery of a graduate-level course in management at two universities via advanced information technology, which was used to enable collaborative learning, teaching with transcontinental student teams and multiple instructors, and integration of external expertise. This partnership enriched student learning and expedited faculty and institutional development. We predict that such transformations will increase as schools of management and institutions of higher learning in general seek to add educational value at low cost.